Adjuvant properties of polymer based on acrylic acid - M. R. Kozak; A. V. Oliynyk; O. S. Zaichenko; V. V. Vlizlo (The Ukrainian Biochemical Journal, 2013)
Adjuvant properties of the polymer containing acrylic acid, glycidyl methacrylate, triethylene glycol methacrylate and butyl acrylate have been established. Antibodies to ovalbumin and bovine serum albumin in the blood of mice were revealed using dot blot analysis and immunoenzyme analysis when applying the investigated polymer as a carrier of these protein antigens. Adjuvant properties of the polymer were compared to aluminum hydroxide, which is a component of many traditional vaccines. Experimental polymer was a stronger adjuvant because it led to an increase of specific antibodies against ovalbumin and bovine serum albumin.